ASSESSMENT OF NURSES/MIDWIVES INVOLVEMENT IN THE ACHIEVEMENT OF THE SUSTAINABLE DEVELOPMENT GOAL 3.8 IN SOUTH-EAST AND SOUTH-WEST, NIGERIA. - Okedo, Henrietta. A.; Philomena N, Nwankwo (International Journal For Research In Health Sciences And Nursing, 2022)
This study assessed the involvement of nurses/midwives in the achievement of the sustainable development goal 3.8 in south-east and south-west, Nigeria. The objective of the study was to investigate the involvement of nurses/midwives in the primary health care setting and how this could help Nigeria in achieving universal health coverage. Also to determine the quality and outcome of nursing care received by the clients/patients in the healthcare facilities. The research design employed in the study was a cross-sectional survey. The population of the study consisted of nurses/midwives and patients attending the facilities during the study in eighteen primary healthcare facilities in Anambra and Lagos states. The sample size consisted of 123 nurses and 202 patients attending the facilities during the study period, who were randomly selected. Purposive judgement was used in determining the health facilities. Data for the study were collected from both primary and secondary sources. The primary data were derived from observations and the administration of copies of the questionnaire. Secondary data were sourced from the five-year facility’s records, previous research works, books, professional journals, and relevant websites. Sirota’s Three-Factor Theory framework of Equity/Fairness, Achievement and Camaraderie was used to examine and explain the critical variables in the study. The instruments used for the study were researcher-developed questionnaire items and a standardized hospital assessment of healthcare providers and systems(HCAHPS) tool. The instruments were validated by the supervisor and other relevant experts from nursing, health management, public health and statistics. Descriptive and inferential statistics were used for data analysis for the generated data. Cronbach alpha was used and the reliability coefficient of 0.86 was derived which is indicative of the reliability of the instrument.